Dimensional and positional temporomandibular joint osseous characteristics in normodivergent facial patterns with and without temporomandibular disorders - Maged S. Alhammadi (14150757) (2023)
Objective This study evaluated the dimensional and positional osseous temporomandibular joint features in normodivergent facial patterns with and without temporomandibular disorders. Methods A total of 165 adult patients were divided into two groups: group 1 (n = 79 patients; 158 joints): temporomandibular disorders patients and group 2 (n = 86 patients; 172 joints): non-temporomandibular disorders patients. Three-dimensional positional and dimensional temporomandibular joint characteristics, including glenoid fossa, mandibular condyles, and joint spaces, were assessed by cone beam computed tomography. Results The glenoid fossa positions in the three orthogonal planes and height showed statistical significance between the two studied groups. The temporomandibular disorders patients showed higher horizontal and vertical condyle inclinations while anteroposterior inclination was less, and the condyle was positioned more superior, anterior, and lateral in the glenoid fossa. The condyle width and length showed no significance between the two groups, while condyle height was smaller in temporomandibular disorders patients. Anterior and medial joint spaces increased while the superior and posterior joint spaces reduced in temporomandibular disorders patients. Conclusion There were significant differences between the patients with and without temporomandibular joint disorders in terms of mandibular fossa positions and height as well as condylar positions and inclinations in horizontal and vertical planes together with reduced condylar height and reduced posterior and superior joint spaces in the temporomandibular disorders patients. Clinical relevance The temporomandibular disorder is a multifactorial disorder in which one of these factors is the dimensional and positional characteristics of the temporomandibular joints; including or excluding this factor requires a comprehensive three-dimensional investigation of patients with TMD compared to the normal group under the condition that the facial pattern is average as a confounding factor. Other Information Published in: Clinical Oral Investigations License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00784-023-05120-0